Study of isolated and combined effects of chloroform and aluminum sulfate with drinking water on hematological indicators of animals - Tomashevska, L.A.; Prokopov, V.O.; KravchunT.Ye., KravchunT.Ye.; Lypovetska, O.B. (Environment & Health, 2023)
Objective: study of the effect of chloroform and aluminum sulfate on hematological indicators of experimental animals.Materials and methods: combined effect of chloroform and aluminum sulfate on hematological indicators.Results: Evaluating the results of research under the conditions of the combined effect of chloroform and aluminum sulfate, it can be stated that the most pronounced changes are observed in groups of animals with the maximum level of load - 3 and 5 MPC, under the conditions of the isolated effect of chloroform and aluminum sulfate, and under the conditions of their combined effect. The detected changes indicate the influence of active factors on the cooperative nature of oxygen binding by hemoglobin, which affects the provision of the transport function of the protein and, accordingly, on the protective function of the group of leukocytes.Changes in the leukogram reflect the phases of the development of protective and adaptive processes in the immune-competent blood system and may indicate the formation of adaptive and adaptive reactions aimed at maintaining the stability of the body’s homeostasis with their subsequent disruption and exhaustion of compensatory mechanisms.Conclusions.The specified changes in the morphological composition of blood can be signs of: violations of physiological processes occurring in the body, slowing down of redox reactions, hypoxic manifestations, reduction and weakening of the immune response and reactivity, which cannot but be reflected in the vital activity and life expectancy of experimental animals.The extrapolation of these results to humans allows us to assume that the population’s constant consumption of drinking water with an excessive content of chloroform and aluminum sulfate over time can lead to changes in the blood system, weakening of the body’s protective immune function and creating conditions for the development of non-infectious pathology.
Keywords: drinking water; chloroform; aluminum sulfate; combined action; еrythrocyte blood system